Infection remediation after septic device extractions: analysis of three treatment strategies including a 1-year follow-up - Burger, Heiko; Strauß, Mona; Chung, Da-Un; Richter, Manfred; Ziegelhöffer, Tibor; Hakmi, Samer; Reichenspurner, Hermann; Choi, Yeong-Hoon; Pecha, Simon (Frontiers in Cardiovascular Medicine, 2024)
Introduction In CIED infections, all device material needs to be removed. But, especially in pacemaker-dependent patients it is often not possible to realize a device-free interval for infection remediation. In those patients, different treatment options are available, however the ideal solution needs still to be defined. Methods This retrospective analysis includes 190 patients undergoing CIED extractions due to infection. Three different treatment algorithms were analyzed: Group 1 included 89 patients with system removal only (System removal group). In Group 2, 28 patients received an epicardial electrode during extraction procedure (Epicardial lead group) while 78 patients in group 3 (contralateral reimplantation group) received implantation of a new system contralaterally during extraction procedure. We analyzed peri- and postoperative data as well as 1-year outcomes of the three groups. Results Patients in the system removal and epicardial lead groups were significantly older, had more comorbidities, and suffered more frequently from systemic infections than those in contralateral reimplantation group. Lead extraction procedures had comparable success rates: 95.5%, 96.4%, and 93.2% of complete lead removal in the System removal, Epicardial Lead, Contralateral re-implantation group respectively. Device reimplantation was performed in all patients in Epicardial lead and Contralateral reimplantation group, whereas only 49.4% in System removal group received device re-implantation. At 1-year follow-up, freedom from infection and absence of pocket irritation were comparable for all groups (94.7% Contralateral reimplantation group and Epicardial lead group, 100% System removal group). No procedure-related mortality was observed, whereas 1-year mortality was 3.4% in System removal group, 4.1% in Contralateral re-implantation group and 21.4% in Epicardial lead group (p < 0.001). Conclusion In patients with CIED infection, systems should be removed completely and reimplanted after infection remediation. In pacemaker-dependent patients, simultaneous contralateral CIED re-implantation or epicardial lead placement may be performed, depending on route, severity and location of infection.